Universal Healthcare Coverage for First Episode of Schizophrenia-Spectrum Disorders in Chile: Analysis of the Administrative Database - Rojas-Moreno, I (Springer Science and Business Media Deutschland GmbH, 2022)
Aim of the study was to analyse the Ministry of Health’s (MINSAL) administrative database of the Universal Health Coverage (UHC) program for First Episode of Schizophrenia Spectrum Disorders (FEP-SSD). The database included every case registered in the program between 2004 and 2017. According to the timeframes established for permanence in the program, cases were defined as Suspected, FEP in diagnostic observation and FEP-SSD. Only first registers were analysed. We compared gender, age at entry, level of care and region where the case was registered. Denominator data for estimation of incidence rates were obtained from the last census. We adjusted incidence rate ratios by age, gender, and region. During the studied period, 33.207 suspected cases were registered. 27.006 (81%) were confirmed as FEP and after 6-month follow-up, 22.701 (68%) were confirmed as FEP-SSD. The median age at entry was 24 years, males entering at younger age. Male proportion was higher than female in all groups. 46.9% of all cases were detected in primary care. FEP-SSD cases were six years younger and had a higher proportion of males than discarded cases (62.6 vs 53.2%). During 169.4 million person-years at risk, crude incidence for suspected cases was 19.58 per 100.000 person-years; for FEP, 15.92 per 100.000 person-years and for FEP-SSD, 13.38 per 100.000 person-years. Chile has lower incidence of FEP-SSD compared to current world estimations but gender proportions are comparable. This UHC program has allowed early access through the integration of mental health to the health network at all levels of care. © 2021, Springer-Verlag GmbH Germany, part of Springer Nature.